2021
DOI: 10.1002/jimd.12356
|View full text |Cite
|
Sign up to set email alerts
|

MRI surveillance of boys with X‐linked adrenoleukodystrophy identified by newborn screening: Meta‐analysis and consensus guidelines

Abstract: Background Among boys with X‐Linked adrenoleukodystrophy, a subset will develop childhood cerebral adrenoleukodystrophy (CCALD). CCALD is typically lethal without hematopoietic stem cell transplant before or soon after symptom onset. We sought to establish evidence‐based guidelines detailing the neuroimaging surveillance of boys with neurologically asymptomatic adrenoleukodystrophy. Methods To establish the most frequent age and diagnostic neuroimaging modality for CCALD, we completed a meta‐analysis of releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 61 publications
1
61
0
Order By: Relevance
“…This discrepancy exemplifies the challenge that our program and our partnering SCCs faced when trying to enforce a uniform approach to monitor these cases when more formal consensus statements were yet to be published. Recommendations were eventually published, but the publication dates were well after screening had begun [14,15,19]. In the interim, our program worked collaboratively with specialists across California and consulted with other state screening programs [25] to provide draft guidelines until a national consensus could be reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy exemplifies the challenge that our program and our partnering SCCs faced when trying to enforce a uniform approach to monitor these cases when more formal consensus statements were yet to be published. Recommendations were eventually published, but the publication dates were well after screening had begun [14,15,19]. In the interim, our program worked collaboratively with specialists across California and consulted with other state screening programs [25] to provide draft guidelines until a national consensus could be reached.…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stem cell transplantation 2 of 13 (HSCT) has been shown to be an effective therapy to halt cerebral demyelination and prevent death if administered early, before neurologic progression [11][12][13]. Regular MRIs and adrenal testing are recommended to monitor for early signs of the disease in order to administer treatment when it is most effective [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Through these efforts, we diagnosed 29 male patients as Addison-only at diagnosis and 43 pre-symptomatic male patients, which led to appropriate follow-up (Figure 2) [8] based on guidelines and references [10][11][12]. More recently, with regard to the timing of starting the MRI follow-up, in order to examine more efficiently and with less burden, it has been suggested that the first examination be done at 12 to 18 months of age, the second after 1 year, and then every 6 months between 3 and 12 years of age [13]. These follow-up efforts lead to steroid replacement therapy and HSCT at the appropriate time to improve the prognosis in male patients with ALD.…”
Section: Efforts To Diagnose Ald Before the Onset Of Cerebral Type At Gifu Universitymentioning
confidence: 99%
“…Follow-up flowchart for patients with pre-symptomatic adrenoleukodystrophy[8]. * start MRI follow-up at 12 to 18 months of age[13].…”
mentioning
confidence: 99%
“…37 The hallmark of structural MRI is the ability to detect cerebral ALD lesions before clinical symptoms become apparent. Therefore, the current recommendation is to repeat brain MRI every 6 months up until the age of 12 years and yearly after that, 12,38 which is a great burden for patients.…”
Section: Structural Mri Brainmentioning
confidence: 99%